2020
DOI: 10.3390/children7100170
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers’ Beliefs towards Children with Autism Spectrum Disorder (ASD) in Yemen

Abstract: It is perplexing that some preschool teachers not only advise parents who have children with autism spectrum disorder (ASD) to go to religious healers, but also attribute such neurological disorders to the curse of the “evil eye” or vaccines. Although it is now the twentieth century, this behavior simply reflects the concerns of over-protective teachers and the cultural misperceptions about the actual definition of ASD. In Yemen, the term “ASD”, with its wide range of symptoms, is still ambiguous among prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In 1987, Stone designed the autism knowledge scale (17) and used it to investigate the knowledge status of parents and teachers about ASD (18). Since then, questionnaires examining the status of knowledge on ASD tailored for specific personnel, such as professionals (15,19) , teachers (9,20), and the general population (11,12) , have revealed that knowledge about ASD is widely lacking. Golson et al conducted a knowledge survey of 318 individuals with no ASD professional training from the general population in the United States in 2022, and 64% of the questions were answered correctly on an average (21).…”
Section: Introductionmentioning
confidence: 99%
“…In 1987, Stone designed the autism knowledge scale (17) and used it to investigate the knowledge status of parents and teachers about ASD (18). Since then, questionnaires examining the status of knowledge on ASD tailored for specific personnel, such as professionals (15,19) , teachers (9,20), and the general population (11,12) , have revealed that knowledge about ASD is widely lacking. Golson et al conducted a knowledge survey of 318 individuals with no ASD professional training from the general population in the United States in 2022, and 64% of the questions were answered correctly on an average (21).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have assessed the knowledge regarding autism spectrum disorders with a lower number of participants than our study and have used lesser variables in their questionnaire. 12 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study emphasizes that the lower the level of teachers' education, the less they know about ASD. 18 Another study measures the awareness about autism among school teachers in Oman in 2013. 40% of teachers thought that autistic children would not express emotions, and 55.5% thought they would not maintain eye contact.…”
Section: Introductionmentioning
confidence: 99%